JENIS TINDAK TUTUR DALAM KHOTBAH JUMAT DI MASJID SYARQI, KAIRO MESIR: KAJIAN PRAGMATIK - Tri Yanti Nurul Hidayati (CMES (Center of Middle Eastern Studies), 2013)
Based on the above, the issues examined in this study is the locution of speech acts,illocution and perlocution in a Friday khotbah by Egyptian native speakers Syeikh Sa‘i>dRuslan with the theme Baina As}-S}u>rah wa Al-H}aqi>qah’ between picture and reality, onApril 25, 2008 in mosque Syarqi> in Manu>fiyyah province, Subkh Ah}ad, Marka>z Asymu>n village, Cairo, Mesir with a pragmatic analysis. The data are sentences containinglocution, illocution and perlocution. The result of analysis shows that speaker of Friday khotbah (khat}i>b) not only use one speech act, but also use some speech acts, that islocution speech act, illocution speech act and perlocution speech act. Locution speech actis the most widely used in Friday khotbah, because it is only used to declare or informsomething. In first and second khotbah, the data of locution speech act is found inopening, content and closing.  The data of illocution speech act is found in opening andcontent, while perlocution speech act is found in closing. Illocution speech act includesFollow-illocutionary in the data message includes assertive (strengthen), directive(prohibiting, commanding), expressive (praise), declaration (testimony), commissive(swear).